Current economic issues in EU integration - Baimbridge, Mark.; Harrop, Jeffrey; Philippidis, G. (George), 1971- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2004)
This book focuses upon a variety of microeconomic and macroeconomic issues, together with considering blue sky scenarios of the future direction of Britain's relationship with the EU. Our principal aim is to introduce readers to a variety of topics covering a broad range of issues relating to the process of European integration agriculture, competition, industry, enlargement, regional and national convergence, central banking.
Includes bibliographical references (p. 209-224) and index.
nmn 09/05/13
Loans
Keywords: Agriculture and state -- European Union countries; Monetary unions -- European Union countries; Europe -- Economic integration; European Union countries -- Economic conditions -- Regional disparities; European Union -- Great Britain